Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Back: Edith Watkins (later married Verlyn Brown) and Francis Fine (later married a Mr. Beasley); Front: Elton Watkins and Charlotte Fine.